Implementation of an English Speaking Learning Application to Strengthen English Literacy for Children with Special Needs at SLBN Pangkalpinang - Diana Anggraeni; Bob Morison Sigalingging; Deni Pratama (Universitas Bangka Belitung, 2026)
English speaking proficiency is a crucial component of global literacy development, including for children with special needs. However, the lack of adaptive learning tools remains a significant challenge in special education environments such as SLBN Pangkalpinang. This community engagement project aimed to implement an English Speaking learning application specifically designed to enhance English language literacy among students with special needs. The activity involved 20 students with special needs and 5 accompanying teachers. The implementation methods included teacher training, application demonstrations, student mentoring, and qualitative evaluations through direct observation and interviews. In addition, a pre-test and post-test design was used to quantitatively assess students’ speaking abilities. The results showed a 42% increase in active student participation and an improvement in the average speaking score from 53.6 to 74.1 after application use, with statistical significance at p < 0.05. Teachers reported that the application facilitated more engaging and effective delivery of English materials and increased student motivation. These findings demonstrate that adaptive technology-based approaches can effectively strengthen foreign language literacy among students with special needs. The community engagement activity highlights the value of responsive and inclusive educational innovations and supports the broader implementation of similar tools across other special education institutions. This initiative emphasizes the importance of equal access to quality education and contributes to inclusive education policy development. This activity demonstrates that Canva can serve as an effective platform for developing inclusive educational content. The implementation of this technology not only addressed learning gaps but also empowered educators with practical digital teaching strategies for special needs education.